2010
DOI: 10.2223/jped.2014
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of human milk donated to a human milk bank before and after measures to reduce the amount of milk unsuitable for consumption

Abstract: Objective: To evaluate the causes of disposal of donated human milk and the impact of the measures taken to reduce the amount of milk unsuitable for consumption. Methods:A quasi-experimental, observational, comparative study was conducted with different populations of external donors in 2006 and 2008. In 2006, a simple form was used to record the criteria for disposal of the donated milk. We also interviewed the donors to find the reason of changes in the milk. In 2008, a checklist containing comprehensive gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
0
11
0
4
Order By: Relevance
“…25,33 Therefore, we would like to emphasize that the recommendations evaluated in this study should be used when the raw milk is expressed, stored, and offered to neonates under trained staff supervision and handled in the hospital environment. Previous studies have shown concerns about raw milk supply to hospitalized infants when milk is expressed and stored at home and later transported to the hospital 33,34 due to negligence with hygiene practices during milk expression, milk mishandling, and household living conditions such as lack of energy, multiple freezer openings, milk stored with other food containers, and long duration of transportation from home to the hospital, among others, resulting in milk unsuitability for consumption.…”
Section: Dornic Titration Showed That Raw Milk Is Suitable For Consummentioning
confidence: 99%
“…25,33 Therefore, we would like to emphasize that the recommendations evaluated in this study should be used when the raw milk is expressed, stored, and offered to neonates under trained staff supervision and handled in the hospital environment. Previous studies have shown concerns about raw milk supply to hospitalized infants when milk is expressed and stored at home and later transported to the hospital 33,34 due to negligence with hygiene practices during milk expression, milk mishandling, and household living conditions such as lack of energy, multiple freezer openings, milk stored with other food containers, and long duration of transportation from home to the hospital, among others, resulting in milk unsuitability for consumption.…”
Section: Dornic Titration Showed That Raw Milk Is Suitable For Consummentioning
confidence: 99%
“…A sujidade se dá quando há qualquer corpo estranho no leite humano, como fragmentos de pele, pêlos e fios de roupa, o que desqualifica o produto para consumo, sendo necessário o descarte de todo o conteúdo do frasco. Existe grande rotatividade de profissionais nos hospitais, o que permite períodos com técnicos sem o devido treinamento, sendo a provável causa para a persistência do resultado do descarte de leite no item de sujidade (22) .…”
Section: Discussionunclassified
“…Grazziotin AL, Grazziotin MCB, Letti LAJ (27) Disposal of human milk donated to a human milk bank before and after measures to reduce the amount of milk unsuitable for consumption Brazil Jornal de pediatria 2010…”
Section: Brazilmentioning
confidence: 99%